Efficacy of rifaximin in the treatment of chronic relapsing diverticulitis - S. I. Achkasov; A. I. Moskalyov; Yu. L. Trubachyova; A. F. Filon (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy of rifaximin in complex conservative treatment of chronic diverticulitis.Material and methods. The main group included 43 patients that received 200 mg rifaximin every 8 h within conservative treatment mode for 14 days. Of all patients 34 were women (79,1%), 9 – men (20,9%), age of patients ranged 44 to 84 years. Severity of clinical symptoms at onset of treatment varied from 1 to 3 points, mean score was 2,11 points (М0=2 points). Extent of inflammatory changes (according to abdominal US or CT with estimation in relation to sigmoid colon axis) varied from 5 to 8 cm, mean – 6,2 cm (М0=6 cm), thickness of muscular layer – from 2 to 5 mm (mean – 2,7 mm, М0=2,5 mm). The control group included 40 patients, who received no rifaximin at conservative treatment. Of all patients 32 were women (80,0%), 8 – men (20,0%), age of patients ranged from 32 to 74 years (mean — 60,9 years, М0=60 years). Severity of clinical symptoms at beginning of treatment varied from 1 to 3 points, 2,18 points mean (М0=2 points). Extent of inflammatory changes varied from 5 to 8 cm, mean – 6,8 cm (М0=6 cm), thickness of muscular layer – from 2 to 5 mm (mean – 2,6 mm, М0=2,5 mm).Results. At the end of 2nd day of treatment intensity of symptoms in main group was 1,55 points, in the control group – 1,69 points (р=0,12). According to US data, no changes in both groups were observed. At the 14th day intensity of clinical symptoms in the main group was 0,26 points (in the control group – 0,71 points; р=0,09). According to results of US in 31 patients of the main group (72,1%) and in 28 controls (70,0%) signs of active inflammation were absent.Conclusions. Rifaximin – is an effective drug for complex conservative treatment of the chronic relapsing diverticulitis, that allows significantly to reduce terms for achievement of complete clinical response.